2021
DOI: 10.12740/app/133639
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anxiety, stress, and burnout symptoms in Brazilian health professionals during the COVID-19 pandemic

Abstract: Aim of the studyOur study aimed to investigate the impacts of the COVID-19 pandemic on Brazilian healthcare workers who work directly with patients diagnosed with COVID-19.Subject or material and methods634 individuals divided into three groups. Non-health workers (n = 372) with a mean age of 36.6 years (SD = 9.14) and 85.5% female; Health Workers (n = 94) with a mean age of 37 years (SD = 7.97) and 90% female; COVID-19 Health Workers (n = 168) with a mean age of 36.23 years (SD = 7.97) and 90% female. We admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…Cluster 1 (red) showed associations between burnout, health professionals and their public health implications. This result is consistent with the findings reported by Suñer-Soler et al (2014), who stated that health professionals are the most affected by burnout and that many of them quit their profession (Grau et al, 2009), along with its financial impact (Bethea et al, 2020), strongly accentuated by COVID-19 (Salvador et al, 2021). Cluster 2 (green) shows the methodological studies on burnout at a Latin American level and which is in line with what Salvagioni reported, who specifies that studies on burnout are developed based on different quantitative (Tabares-Díaz et al, 2020) and qualitative (Kulakova et al, 2017) methodologies and tools used to measure burnout (Salvagioni et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Cluster 1 (red) showed associations between burnout, health professionals and their public health implications. This result is consistent with the findings reported by Suñer-Soler et al (2014), who stated that health professionals are the most affected by burnout and that many of them quit their profession (Grau et al, 2009), along with its financial impact (Bethea et al, 2020), strongly accentuated by COVID-19 (Salvador et al, 2021). Cluster 2 (green) shows the methodological studies on burnout at a Latin American level and which is in line with what Salvagioni reported, who specifies that studies on burnout are developed based on different quantitative (Tabares-Díaz et al, 2020) and qualitative (Kulakova et al, 2017) methodologies and tools used to measure burnout (Salvagioni et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Brazil is the country that has contributed the most with 48.31%.This result is in line with the data shown in studies on burnout syndrome among Latin American teachers (Tabares-Díaz et al, 2020) and physicians (Buitrago et al, 2020). This is also interesting because Brazil is one of the countries most affected by COVID-19 (Salvador et al, 2021) and, therefore, Brazilian workers have suffered a greater blow due to the pandemic (Moreira & Lucca, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It consists of 20 items in a four-factor structure: Enthusiasm towards work, Psychological exhaustion, Indolence, Guilt. The answer key is a five-point Likert scale from 0 "never" to 4 "very often " [9]. COVID-19 Burnout Scale (COVID-19-BS)is a scale developed by Yıldırım and Solmaz ( 2020) that consists of 10 items and each item is rated with a 5-point Likert type scale ranging from 1 = never to 5 = always.…”
Section: Tools Used To Measure Burnout Associated With Covid-19mentioning
confidence: 99%
“…The group of health care workers struggling with COVID-19 showed higher levels of anxiety and mental exhaustion than the other groups (non-COVID-19 health care workers, non-health care workers).Interestingly, the overall scores for job burnout and post-traumatic stress showed no statistically significant differences and anxiety was the most differentiating factor. Employees struggling on the front lines are characterized by greater anxiety about the future [9]. Among Italian health care workers, those at high risk of burnout had lower resilience and greater difficulty coping with the uncertainty associated with the current SARSCoV-2 outbreak than the low burnout risk group [6].…”
Section: Burnout Among Healthcare Workersmentioning
confidence: 99%